The life of Luigi Giussani - Savorana, Alberto (ACUP E-Book., 2018)
"Monsignor Luigi Giussani (1922 2005) was the founder of the Catholic lay movement Communion and Liberation in Italy, which has hundreds of thousands of adherents around the globe. In Luigi Giussani, His Life Alberto Savorana, who spent an important part of his life working and studying with Giussani, draws on many unpublished documents to recount who the priest was and how he lived. Giussani's life story is particularly significant because it shares many of the same challenges, risks, and paths toward enlightenment that are described in his numerous and influential publications. Savorana demonstrates that the circumstances Giussani experienced and the people he encountered played a crucial role in defining his vocation. Illuminating details are shared about Giussani's parents, professors, and friends in the seminary, the things he read, his priesthood, his experience teaching, misunderstandings and moments of recognition, and illness. Luigi Giussani considered Christianity to be a fact, a real event in human life, which takes the form of an encounter, inviting anyone and everyone to verify its relevance to life's needs. This is what happened for so many people all over the world, who recognized in this priest and leader, with his rough and captivating voice, not only a teacher to learn from, but above all a man to compare oneself with--a companion for the journey who could be trusted to answer the question: how can we live? In addition to providing the first chronological reconstruction of the life of the founder of Communion and Liberation, Luigi Giussani, His Life provides a detailed account of his legacy and what his life's work meant to individual people and the Church."--